Knowledge and Preventive Behaviors Toward the Coronavirus (COVID-19) Pandemic Among Adults Population: A Cross-Sectional Study in Iraq - Abdullah Athbi , Hassan; A. Athbee Almalike , Malik; Khelf Kitab , Hussein (Kerbala Journal of Nursing and Health Sciences., 2025)
Introduction: Coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an infectious disease. The political decisions have been exerted together with personal knowledge and behaviors to emphasize the community global efforts to prevent the spreading of disease. This study was performed to identify the public knowledge and behavioral responses about the outbreak of COVID-19. Methods: A cross-sectional study was performed from the period of 15th May 2020 to 20th July 2022 among Iraqi populations. A convenience sampling consist of 1943 participants were involved in this survey. The data were collected through an online questionnaire by using a Google Form; the data were investigated by using the SPSS program Version 25. Results: The study results expose a high knowledge level about symptoms related to COVID-19; the mean score of knowledge was (1.5). In addition to that, the result reveals a high level of participants' behaviors to confront the preventing transmission of COVID-19; about 95.0% of participants perform hand washing frequently, 90.0%, 84.8%, and 80.2% avoid participate in social events, maintain social distance and prevent contact with infected persons, and prevent contact with any persons respectively, and 70.0% of participants reschedule or cancel travel plans as preventing behavior to avoid the COVID-19 transmission. Conclusion: Our study concludes a high knowledge level of the COVID-19 symptoms, and a high level of behaviors to prevent the spreading of COVID-19, also many factors can prevent of home quarantine and social isolation to avoid the spreading of COVID-19 among Iraqi residents from these factors the need for daily income, the need for health care outside the home.